Reducing Media-Induced Mass Killings: Lessons From Suicide Prevention. (February 2018) - Meindl, James N.; Ivy, Jonathan W.
A mass killing is a complex behavior that is the product of a range of variables. Recent research suggests one such variable by showing that when a mass killing occurs there is a heightened chance of another occurring in the near future. This increase in probability has been referred to as contagion and one possible mechanism for contagion may be generalized imitation. Generalized imitation requires the presence of some model to prompt imitation, and we suggest media reporting methods as a prominent model inspiring future mass killings. This article analyzes mass killings as the culmination of a sequence of thoughts and actions that are influenced by environmental events including media reports of mass killings. We then evaluate media reporting guidelines and research related to the prevention of suicide and other imitational behaviors to identify reactive and proactive strategies that could minimize the likelihood of one mass killing inducing another.